Prenatal Exposure to Progesterone Affects Sexual Orientation in Humans - Reinisch, June M.; Mortensen, Erik Lykke; Sanders, Stephanie A. (Archives of sexual behavior, 2017)
Prenatal sex hormone levels affect physical and behavioral sexual differentiation in animals and humans. Although prenatal hormones are theorized to influence sexual orientation in humans, evidence is sparse. Sexual orientation variables for 34 prenatally progesterone-exposed subjects (17 males and 17 females) were compared to matched controls ( M age = 23.2 years). A case–control double-blind design was used drawing on existing data from the US/Denmark Prenatal Development Project. Index cases were exposed to lutocyclin (bioidentical progesterone = C 21 H 30 O 2 ; M W : 314.46) and no other hormonal preparation. Controls were matched on 14 physical, medical, and socioeconomic variables. A structured interview conducted by a psychologist and self-administered questionnaires were used to collect data on sexual orientation, self-identification, attraction to the same and other sex, and history of sexual behavior with each sex. Compared to the unexposed, fewer exposed males and females identified as heterosexual and more of them reported histories of same-sex sexual behavior, attraction to the same or both sexes, and scored higher on attraction to males. Measures of heterosexual behavior and scores on attraction to females did not differ significantly by exposure. We conclude that, regardless of sex, exposure appeared to be associated with higher rates of bisexuality. Prenatal progesterone may be an underappreciated epigenetic factor in human sexual and psychosexual development and, in light of the current prevalence of progesterone treatment during pregnancy for a variety of pregnancy complications, warrants further investigation. These data on the effects of prenatal exposure to exogenous progesterone also suggest a potential role for natural early perturbations in progesterone levels in the development of sexual orientation.